Biopolymer-enhanced nanoemulsions for controlled release of thyme: Impact on strawberry shelf life and quality - Leila Heidary; Himan Nourbakhsh; Zahra Javanmardi; Mahmoud Koushesh Saba (Journal of Agriculture and Food Research)
The development of natural, edible coatings is essential for enhancing postharvest fruit preservation while reducing reliance on synthetic preservatives. In this study, a multi-functional coating combining thyme-loaded nanoemulsion (Nano-EM-Thy) with chitosan (CH) and carboxymethyl cellulose (CMC) was formulated to extend the shelf life of strawberries. Water-in-oil nanoemulsions were prepared with the oil (containing medium chain triglyceride oil (MCT) with Thy), tween 80, and water (containing one or both biopolymers) at a mass ratio of 2:4:94 using a spontaneous emulsification method, achieving droplet sizes ranging from 60.45 to 106 nm. The nanoemulsion exhibited strong antimicrobial, effectively controlling Botrytis cinerea growth and maintaining fruit quality. Coatings containing Nano-EM-Thy, CH, and CMC significantly reduced weight loss (1.7 %), preserved firmness (3.6 N), and stabilized anthocyanin content over 15 days of storage at 4 °C. This composite coating extended the shelf life of strawberries by maintaining their physicochemical properties and reducing microbial spoilage, presenting a promising approach for natural postharvest preservation strategies.